Diabetic Control among Type 2 Diabetes Mellitus (T2DM) Patients before and after the Implementation of Movement Control Order (MCO) due to COVID-19 Pandemic - Narwani Hussin; Sreevali Muthuvadivelu; Chan Wai Seong; Nurul Najiha Jafery (Asian Journal of Medicine & Health Sciences, 2022)
Background: The implementation of MCO had changed the routine appointments in clinics and hospital visits, which indirectly affect the management of diabetic patients. In addition, people with diabetes have been reported to have a higher risk of mortality due to COVID-19 infection. This study aims to assess the diabetic control among T2DM patients before and after the implementation of MCO due to the COVID-19 pandemic. Methods: This was a retrospective study. Medical records from adult T2DM patients who had follow-up visits to Medical Outpatient Department (MOPD) clinic, Hospital Taiping from December 2019 until August 2020 were reviewed. The calculated sample size was 97 patients. Their weight, blood pressure (BP) and blood parameters before and after MCO were compared. Results: Ninety-nine records were reviewed. The mean age of the patient was 56 years (SD 12.06). 54 (54.5%) were female. Majority were Malays; 71 (71.7%). There was no significant difference in mean BP and weight pre and post MCO. Most of the blood parameter results (FBS, Urea, Creatinine, Total Cholesterol, LDL and Triglycerides) showed no significant difference before and after the implementation of MCO. However, HDL showed significant difference in the result with pre MCO of 1.17mmol/L (SD 0.35) and post MCO of 1.22mmol/L (SD 0.34); p value 0.012. In addition, HbA1c also showed slight improvement with pre value of 8.89% (SD 2.35) and post value of 8.47% (SD 2.24), p value 0.020. Conclusion: This study showed that the implementation of MCO had a slight impact on diabetic control of T2DM patients in our study population.